Optimasi Pola Pengasuhan Digital dalam Pemenuhan Kebutuhan Informasi - Mutia Rahmi Pratiwi; Heni Indrayani; Swita Amalia (Expose: Jurnal Ilmu Komunikasi, 2020)
The implementation of parenting uses digital content to become the major source to gather information, in particular, parents these days. Digital parenting appears not only to provide the information that parents need but also to acknowledge about parenting through digital media. Moreover, the information is enlightenment and experienced by other parents so that it helps to use digital media. This paper examines the effect of digital parenting optimization and the fulfilment information need by the parents. This explanatory quantitative study was conducted with 100 parents that joined the parenting community and practiced the parenting pattern with a digital media platform to access the information. Furthermore, this study applied the purposive sampling technique. Data analyzing technique is to test the hypothesis with the simple linear regression model. The result of this study shows that the relation between digital parenting and fulfilment information need by the parents is significantly correlated. Also, the value of the correlation coefficient in the medium range is R =04,16 influence to the low range (0.173). Eventually, to fulfil the information for the parent need is not only gain by digital access.